UDRP UDRP: The Best Way to Solve Domain Dispute? UDRP: The Best Way to Solve Domain Dispute? - Hariandi Maulid (PPM Universitas Logistik dan Bisnis Internasional, 2014)
The proliferation of Internet technology, without doubt, is helping people to become a communication and information switchboard, between persons, networks, busines, as well as institutions. It is done by an Internet Domain Name, an alpha numeric mnemonic device that can be mapped onto an Internet Protocol (IP) address to ease users browsing and surfing the web. This domain can be a valuable business asset as it often consist of a person’s name or company’s name or trademark. The dispute may arise when one party claims other’s domain names which considered tend to dilute his/her trademark by many different offences. This paper investigates how Uniform Dispute Resolution Policy (UDRP), first coined by ICANN, comes with solution to the dispute as well as its good side and shortcomings.